Islamic Legal Literature and Substantive Law in Indonesia - Lubis, Nur Ahmad Fadhil (Studia Islamika, 1997)
This article discusses the development and diversity of thought and practice of Islamic law Muslims in Indonesia, particularly in the areas of family and inheritance. In discussing Islamic law (shari'a or fiqh), the main focus of this paper is the position and contribution of Islamic law in the context of the national legal system. To that end, the proposed law reform and successfully passed will be used as the unit of analysis, in particular two of the New Order government legislation, namely marriage law in 1974 and 1991 Compilation of Islamic Law.DOI: 10.15408/sdi.v4i4.765